Relevansi Pancasila dalam Pembentukan Hukum Islam di Indonesia : Perspektif Sinkretisme Hukum - Ashfiya Nur Atqiya; Ahmad Muhamad Musain Nasoha; Iqbal Ubaidillah; Nabil Dwi Nurjannah; Tiara Amalia; Miftah Nurlina Mufida (Asosiasi Penelitian dan Pengajar Ilmu Hukum Indonesia, 2025)
This study aims to explore the relevance of Pancasila in the formation of Islamic law in Indonesia through the perspective of legal syncretism. Using qualitative research methods and a normative approach, this study analyzes the interaction between the values of Pancasila and the principles of Islamic law in an effort to create a harmonious and inclusive legal system. In the Indonesian context, Pancasila as the state ideology plays an important role as a normative framework that can integrate Islamic law with national principles, such as justice, unity, humanity and divinity.Through a literature study and in-depth interviews with jurists and theologians, this research found that there is harmony between the values of Pancasila and the basic principles of Islamic law, which allows for legal syncretism. In addition, this research shows that the application of legal syncretism can be a solution in overcoming challenges arising from differences in the interpretation and application of Islamic law within the framework of the Pancasila state. The research also concludes that strengthening legal syncretism through a normative approach can support the development of a legal system that is more adaptive and responsive to the dynamics of Indonesia's multicultural and multireligious society.